Talcum powder-wollastonite master batch and preparation method thereof

Through the preparation of talc powder-silicon ash mother grains, combined with the compatibility of modified powder and resin, the problem of poor environmental protection and lack of mechanical properties of degradable plastic products and lack of mechanical properties, and realized high environmental protection and high-mechanical performance meals. Box production.

CN119371789AActive Publication Date: 2025-01-28JIANGXI HONGYI POLYMERIC MATERIALS +1

Patent Information

Application Number
CN202411633842.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-28
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The production process of existing biodegradable plastic products is poor in environmental protection and insufficient mechanical properties. Especially in the production of disposable lunch boxes, it is difficult to meet the requirements of high environmental protection and high mechanical properties.

Method used

The use of talc powder-silicon ash mother grains, consisting of polylactic acid, modified talc powder, modified silicon ash powder, antioxidants, stearic acid and lubricant. The mechanical performance of the box reduces dust pollution through closed production equipment.

Benefits of technology

The production of dust -free production has been realized, the mechanical performance and environmental protection of the lunch box is improved, and the problems of the environmental protection of plastic products can be degraded in existing technologies and insufficient mechanical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005138166020000081
    Figure BDA0005138166020000081
Patent Text Reader

Abstract

The invention provides a talcum powder-wollastonite master batch and a preparation method thereof, and belongs to the technical field of preparation of master batches for biodegradable plastics. Modified talcum powder, modified wollastonite powder, polylactic acid, an antioxidant, stearic acid and a lubricant are used as raw materials, a talcum powder and wollastonite processing production line and master batch production equipment are combined for use, and a master batch finished product is directly produced from talcum powder and wollastonite raw ore in a one-stop mode. The talcum powder-wollastonite master batch disclosed by the invention has excellent mechanical properties, and the preparation method of the talcum powder-wollastonite master batch reduces dust pollution in intermediate powder packaging and powder transportation, loading and unloading processes, and saves process energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of master batches for biodegradable plastics, in particular to a talc-wollastonite master batch and a preparation method thereof. Background Art

[0002] The application of degradable plastics has become a trend. Plastic products used in the past are non-degradable or slow to degrade, and the pollution to the environment after being discarded has always been a thorny problem. With the enhancement of the public's environmental awareness, degradable plastic products are becoming more and more popular among the public. In addition, the continuous increase in environmental protection efforts and the derivation of national policies have made degradable plastics a subject of extensive research by scholars in recent years, and a number of degradable plastic manufacturers have emerged on the market. Biodegradable plastics refer to plastics that can be degraded under the action of microorganisms existing in nature. Ideal biodegradable plastics can not only be completely decomposed by environmental microorganisms, but also have excellent performance. The existing use scenarios of plastic products mainly appear in supermarket shopping bags, disposable lunch boxes, ground films, agricultural films, etc. Because of their high frequency of use, they need to be degradable, otherwise it will cause serious "white pollution" problems. Some provinces have issued relevant policies and must use degradable products.

[0003] Nowadays, take-out has become an important part of the catering industry, which has led to a continuous increase in the demand for disposable lunch boxes. Disposable lunch boxes are currently common degradable plastic products. Due to the late start in this field, there are not many domestic manufacturers that produce such degradable disposable lunch boxes, and there is room for improvement in technology and raw material optimization. The lunch box itself is linked to catering, and as long as the product involves food, the environmental protection requirements will be higher. At present, manufacturers are often faced with the problem of excessive dust in the production workshop due to the dust problem caused by powder fillers such as calcium carbonate and talcum powder used in the production process. It is difficult to solve the problem, and the dust produced in the production workshop is often excessive, which makes it difficult for the food-grade lunch boxes produced to pass the environmental impact assessment. To achieve dust-free production, converting powder into masterbatch is currently the ideal way; on the other hand, there are more and more disposable use scenarios, and the existing technology has also put forward higher requirements on the mechanical properties of lunch boxes. How to improve the mechanical properties of lunch boxes while ensuring that the gram weight of lunch boxes meets the standard is also a difficult problem currently faced. Summary of the invention

[0004] The purpose of the present invention is to provide a talc-wollastonite masterbatch and a preparation method thereof, which are used to solve the technical problems in the prior art that the production process of degradable plastic products is poor in environmental protection and the mechanical properties of the degradable plastic products are insufficient.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a talc-wollastonite masterbatch, which is composed of the following components in parts by mass: 45-55 parts of polylactic acid, 25-35 parts of modified talc, 12-16 parts of modified wollastonite powder, 0.5-2 parts of antioxidant, 2-4 parts of stearic acid and 2-4 parts of lubricant.

[0007] Furthermore, the number average molecular weight of the polylactic acid is 100,000 to 150,000.

[0008] Further, the antioxidant includes one or more of butylated hydroxyanisole, tert-butyl-4-hydroxyanisole and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate;

[0009] The lubricant includes one or more of calcium stearate, glyceryl stearate and PE wax.

[0010] The present invention provides a method for preparing the above-mentioned talc-wollastonite masterbatch, comprising the following steps:

[0011] Step 1): crushing talc ore to obtain talc powder, and then mixing it with coconut oil to obtain modified talc powder; crushing wollastonite ore to obtain wollastonite powder, and then mixing it with coconut oil to obtain modified wollastonite powder;

[0012] Step 2): Modified talc powder, modified wollastonite powder, polylactic acid, antioxidant, stearic acid and lubricant are mixed, and the obtained mixture is extruded and pelletized to obtain talc powder-wollastonite masterbatch.

[0013] Furthermore, in step 1), the particle size of the talcum powder is 1000-1500 mesh, and the amount of coconut oil added is 0.8-1% of the mass of the talcum powder;

[0014] The mixing is carried out under stirring, and the stirring speed is 3000-3600r / min.

[0015] Furthermore, in step 1), the particle size of the wollastonite powder is 600-800 mesh, and the amount of coconut oil added is 0.8-1% of the mass of the wollastonite powder;

[0016] The mixing is carried out under stirring, and the stirring speed is 3000-3600r / min.

[0017] Furthermore, in step 2), the mixing is carried out under stirring, the stirring speed is 1000-1200 r / min, and the stirring time is 3-8 min;

[0018] The temperature of the mixture is 120-130° C.;

[0019] The extrusion is carried out in an extruder, the speed of the extruder is 650-750 r / min, and the feeding speed is 45-50 r / min;

[0020] The extruder comprises 10 working sections, wherein the temperatures of the 10 working sections are independently 170-185°C, and the head temperature is 180-190°C.

[0021] Furthermore, in step 2), the pelletizing is performed by water ring hot cutting process, and the length of the obtained masterbatch is 3 to 5 mm.

[0022] Technical effects of the present invention:

[0023] The present invention adopts closed and continuous production equipment, directly from raw ore to product masterbatch, reducing the dust pollution in the intermediate powder packaging and powder transportation and loading and unloading process, saving process energy consumption;

[0024] After talcum powder and wollastonite powder are modified, the surface-coated modifier coconut oil not only plays a lubricating role at high temperature, which is conducive to processing, but also, compared with the direct mixing and processing production method of unmodified powder, modifier and resin, the addition of modifier can improve the compatibility of powder and matrix resin.

[0025] Wollastonite powder with a high aspect ratio is selected and combined with talc powder to prepare a masterbatch and applied to the production of lunch boxes. The needle-like structure of wollastonite can increase the toughness of the lunch box, and together with the talc powder with a flaky structure, a fluffy network structure is constructed. Compared with the prior art, the masterbatch of the present invention is used to produce lunch boxes of the same weight, which reduces the density of the lunch box while increasing the thickness, further increasing the strength of the lunch box. DETAILED DESCRIPTION

[0026] The invention provides a talc-wollastonite masterbatch, which is composed of the following components in parts by mass: 45-55 parts of polylactic acid, 25-35 parts of modified talc, 12-16 parts of modified wollastonite powder, 0.5-2 parts of antioxidant, 2-4 parts of stearic acid and 2-4 parts of lubricant.

[0027] In the present invention, based on the mass percentage, the polylactic acid is preferably 48 to 52 parts, and more preferably 50 parts; the modified talc is preferably 27 to 33 parts, and more preferably 30 parts; the modified wollastonite is preferably 13 to 14 parts, and more preferably 13.5 parts; the antioxidant is preferably 1 to 1.8 parts, and more preferably 1.5 parts; the stearic acid is preferably 2.5 to 3.5 parts, and more preferably 3 parts; the lubricant is preferably 2.5 to 3.5 parts, and more preferably 3 parts.

[0028] In the present invention, the number average molecular weight of the polylactic acid is 100,000 to 150,000, preferably 120,000.

[0029] In the present invention, the melting point of the polylactic acid is 175°C and the glass transition temperature is 60°C.

[0030] In the present invention, the antioxidant includes one or more of butylated hydroxyanisole, tert-butyl-4-hydroxyanisole and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, preferably butylated hydroxyanisole, tert-butyl-4-hydroxyanisole or β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester, further preferably butylated hydroxyanisole or tert-butyl-4-hydroxyanisole, more preferably butylated hydroxyanisole;

[0031] The lubricant includes one or more of calcium stearate, glyceryl stearate and PE wax, preferably calcium stearate, glyceryl stearate or PE wax, more preferably calcium stearate or glyceryl stearate, and more preferably calcium stearate.

[0032] The present invention provides a method for preparing the above-mentioned talc-wollastonite masterbatch, comprising the following steps:

[0033] Step 1): crushing talc ore to obtain talc powder, and then mixing it with coconut oil to obtain modified talc powder; crushing wollastonite ore to obtain wollastonite powder, and then mixing it with coconut oil to obtain modified wollastonite powder;

[0034] Step 2): Modified talc powder, modified wollastonite powder, polylactic acid, antioxidant, stearic acid and lubricant are mixed, and the obtained mixture is extruded and pelletized to obtain talc powder-wollastonite masterbatch.

[0035] In the present invention, in step 1), the particle size of the talc is 1000-1500 mesh, preferably 1200-1400 mesh, and more preferably 1300 mesh, and the amount of coconut oil added is 0.8-1% of the mass of the talc, preferably 0.9%;

[0036] The mixing is performed under stirring, and the stirring speed is 3000-3600 r / min, preferably 3200-3400 r / min, and more preferably 3300 r / min.

[0037] In the present invention, in step 1), the particle size of the wollastonite powder is 600-800 mesh, preferably 700 mesh, and the amount of coconut oil added is 0.8-1% of the mass of talc powder, preferably 0.9%;

[0038] The mixing is performed under stirring, and the stirring speed is 3000-3600 r / min, preferably 3200-3400 r / min, and more preferably 3300 r / min.

[0039] In the present invention, the talc ore is preferably a high-purity talc ore with a whiteness of ≥92% and a silicon content of ≥65%. The crushing is firstly coarse crushing to crushed stones with a diameter of ≤6 cm, and then dry grinding into talc powder by Yifeng grinding.

[0040] In the present invention, the wollastonite ore is preferably a high-purity wollastonite ore with a whiteness of ≥91% and a silicon dioxide content of ≥53%. The crushing is firstly coarsely crushed into broken stones with a diameter of ≤6 cm, and then ground into wollastonite powder by air jet mill dry method.

[0041] In the present invention, the modification of talc and wollastonite is carried out in a high-speed mixer, and the coconut oil is preferably heated and melted to a liquid state of 40 to 60°C.

[0042] In the present invention, in step 2), the mixing is carried out under stirring, the stirring speed is 1000-1200 r / min, preferably 1100 r / min, and the stirring time is 3-8 min, preferably 5 min;

[0043] The temperature of the mixture is 120-130°C, preferably 125°C;

[0044] The extrusion is carried out in an extruder, the speed of the extruder is 650-750 r / min, preferably 700 r / min, and the feeding speed is 45-50 r / min, preferably 48 r / min;

[0045] The extruder comprises 10 working sections, wherein the temperatures of the 10 working sections are independently 170-185°C, preferably 172-180°C, more preferably 175°C, and the head temperature is 180-190°C, preferably 185°C.

[0046] In the present invention, in step 2), the pelletizing is performed by water ring hot cutting process, and the length of the obtained masterbatch is 3 to 5 mm, preferably 4 mm.

[0047] In the present invention, in step 2), the materials are mixed evenly in a high-speed mixer and then transported to another silo. The outlet of the silo containing the mixture is connected to the feed silo of the twin-screw extruder. The mixture is fed into the silo of the extruder by an automatic weighing and batching system, and then extruded and pelletized by the extruder.

[0048] In the present invention, the processing, modification and masterbatch production equipment of talcum powder ore and wollastonite ore are used in conjunction, and the production from ore to masterbatch is closed, without powder packaging and transportation in the middle, so dust pollution can be avoided.

[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0050] Example 1

[0051] The talc ore with a whiteness of 92% and a silicon content of 65% is roughly broken and ground to obtain talc powder of 1000 mesh, the talc powder is mixed with coconut oil at a temperature of 40° C. and an addition amount of 0.8wt% (calculated as talc powder), and stirred at a speed of 3000 r / min to obtain modified talc powder; the wollastonite ore with a whiteness of 92% and a silicon dioxide content of 54% is roughly broken and ground to obtain wollastonite powder of 600 mesh, the wollastonite powder is mixed with coconut oil at a temperature of 40° C. and an addition amount of 0.8wt% (calculated as wollastonite powder), and stirred at a speed of 3000 r / min to obtain modified wollastonite powder;

[0052] 50 parts of polylactic acid resin with a number average molecular weight of 100,000, 30 parts of modified talc, 14 parts of modified wollastonite powder, 1 part of butylated hydroxyanisole, 2 parts of stearic acid and 3 parts of stearyl glyceride were put into a high-speed mixer and mixed at a speed of 1000 r / min for 5 minutes. The resulting mixture with a temperature of 120°C was put into a twin-screw extruder with a speed of 700 r / min, a feeding speed of 50 r / min and a head temperature of 180°C (the temperatures of the 10 working sections of the twin-screw extruder are: 175°C in zone 1, 175°C in zone 2, 175°C in zone 3, 175°C in zone 4, 175°C in zone 5, 180°C in zone 6, 180°C in zone 7, 185°C in zone 8, 180°C in zone 9 and 180°C in zone 10) for extrusion, and then pelletized through a hydrothermal ring cutting process to obtain talc-wollastonite masterbatch with a length of 3 mm.

[0053] Example 2

[0054] The talc ore with a whiteness of 93% and a silicon content of 67% is roughly broken and ground to obtain talc powder of 1000 mesh, the talc powder is mixed with coconut oil at a temperature of 60° C. and an addition amount of 1wt% (calculated as talc powder), and stirred at a speed of 3600 r / min to obtain modified talc powder; the wollastonite ore with a whiteness of 93% and a silicon dioxide content of 56% is roughly broken and ground to obtain wollastonite powder of 800 mesh, the wollastonite powder is mixed with coconut oil at a temperature of 60° C. and an addition amount of 1wt% (calculated as wollastonite powder), and stirred at a speed of 3600 r / min to obtain modified wollastonite powder;

[0055] 50 parts of polylactic acid resin with a number average molecular weight of 150,000, 30 parts of modified talc, 14 parts of modified wollastonite powder, 1 part of butylated hydroxyanisole, 2 parts of stearic acid and 3 parts of PE wax were put into a high-speed mixer and mixed at a speed of 1100 r / min for 8 minutes. The resulting mixture with a temperature of 130°C was put into a twin-screw extruder with a speed of 650 r / min, a feeding speed of 45 r / min and a head temperature of 190°C (the temperatures of the 10 working sections of the twin-screw extruder are: 175°C in zone 1, 175°C in zone 2, 175°C in zone 3, 175°C in zone 4, 175°C in zone 5, 180°C in zone 6, 180°C in zone 7, 185°C in zone 8, 180°C in zone 9 and 180°C in zone 10) for extrusion, and then pelletized through a hydrothermal ring cutting process to obtain talc-wollastonite masterbatch with a length of 5 mm.

[0056] Example 3

[0057] The talc ore with a whiteness of 92% and a silicon content of 65% is roughly broken and ground to obtain talc powder of 1500 mesh, the talc powder is mixed with coconut oil at a temperature of 50° C. and an addition amount of 0.8wt% (calculated as talc powder), and stirred at a speed of 3000 r / min to obtain modified talc powder; the wollastonite ore with a whiteness of 92% and a silicon dioxide content of 55% is roughly broken and ground to obtain wollastonite powder of 800 mesh, the wollastonite powder is mixed with coconut oil at a temperature of 50° C. and an addition amount of 0.8wt% (calculated as wollastonite powder), and stirred at a speed of 3000 r / min to obtain modified wollastonite powder;

[0058] 55 parts of polylactic acid resin with a number average molecular weight of 150,000, 35 parts of modified talc, 16 parts of modified wollastonite powder, 2 parts of tert-butyl-4-hydroxyanisole, 4 parts of stearic acid and 4 parts of calcium stearate were put into a high-speed mixer and mixed at a speed of 1200 r / min for 5 minutes. The resulting mixture with a temperature of 120° C. was put into a twin-screw extruder with a speed of 750 r / min, a feeding speed of 50 r / min and a head temperature of 180° C. (the temperatures of the 10 working sections of the twin-screw extruder are: 170° C. in zone 1, 173° C. in zone 2, 175° C. in zone 3, 175° C. in zone 4, 178° C. in zone 5, 180° C. in zone 6, 180° C. in zone 7, 185° C. in zone 8, 180° C. in zone 9 and 180° C. in zone 10) for extrusion, and then pelletized through a hydrothermal ring cutting process to obtain talc-wollastonite masterbatch with a length of 3 mm.

[0059] Comparative Example 1

[0060] The talc ore with a whiteness of 92% and a silicon content of 65% is roughly crushed and ground to obtain talc powder with a mesh size of 1250; the wollastonite ore with a whiteness of 92% and a silicon dioxide content of 54% is roughly crushed and ground to obtain wollastonite powder with a mesh size of 600;

[0061] 50 parts of polylactic acid resin with a number average molecular weight of 100,000, 30 parts of talc, 14 parts of wollastonite powder, 1 part of butylated hydroxyanisole, 2 parts of stearic acid and 3 parts of glyceryl stearate are put into a high-speed mixer and mixed at a speed of 1000 r / min for 5 minutes. The resulting mixture with a temperature of 120°C is put into a twin-screw extruder with a speed of 700 r / min, a feeding speed of 50 r / min and a head temperature of 180°C (the temperatures of the 10 working sections of the twin-screw extruder are: 175°C in zone 1, 175°C in zone 2, 175°C in zone 3, 175°C in zone 4, 175°C in zone 5, 180°C in zone 6, 180°C in zone 7, 185°C in zone 8, 180°C in zone 9 and 180°C in zone 10) for extrusion, and then pelletized through a hydrothermal ring cutting process to obtain talc-wollastonite masterbatch with a length of 3 mm.

[0062] Comparative Example 2

[0063] The talc ore with a whiteness of 92% and a silicon content of 65% was coarsely crushed and ground to obtain talc powder with a mesh size of 1250, and the talc powder was mixed with coconut oil at a temperature of 40° C. and an addition amount of 1 wt % (calculated as talc powder), and stirred at a speed of 3000 r / min to obtain modified talc powder;

[0064] 50 parts of polylactic acid resin with a number average molecular weight of 100,000, 44 parts of modified talc, 1 part of butyl hydroxyanisole, 2 parts of stearic acid and 3 parts of stearyl glyceride were put into a high-speed mixer and mixed at a speed of 1200 r / min for 5 minutes. The resulting mixture with a temperature of 120°C was put into a twin-screw extruder with a speed of 700 r / min, a feeding speed of 50 r / min and a head temperature of 180°C (the temperatures of the 10 working sections of the twin-screw extruder are: zone 1 175°C, zone 2 175°C, zone 3 175°C, zone 4 175°C, zone 5 175°C, zone 6 180°C, zone 7 180°C, zone 8 185°C, zone 9 180°C, and zone 10 180°C) for extrusion, and then pelletized through a hydrothermal ring cutting process to obtain talc masterbatch with a length of 3 mm.

[0065] The masterbatches obtained in Examples 1 to 2 and Comparative Examples 1 to 2 were used to produce disposable degradable lunch boxes. The masterbatches and 0.8 wt % of a composite modified foaming agent (mass ratio AC180: ZnO: Zn(St)) were mixed by chemical foaming injection molding. 2 =6:1:1) mixed evenly and added into the injection molding machine. The working parameters of the injection molding machine are: injection volume 102g, injection speed 65cm 3 / sec, the injection pressure is 160MPa, and injection molded samples of the same specifications are obtained. The tensile and bending properties of the samples are tested according to the national standards GB / T1040.1-2006 and GB / T9341-2008. Table 1 shows the performance test results of the injection molded samples produced by the masterbatch obtained in Examples 1-2 and Comparative Examples 1-2.

[0066] Table 1 Performance test results of the samples obtained by producing the masterbatch of Examples 1 to 2 and Comparative Examples 1 to 2

[0067]

[0068] It can be seen from Table 1 that the tensile strength and bending strength of the spline in Comparative Example 1 are lower than those in Examples 1 and 2, indicating that talc and wollastonite can improve the mechanical properties of the lunch box after modification; the tensile strength and bending strength of the spline in Comparative Example 1 are higher than those in Comparative Example 2, indicating that the addition of wollastonite can improve the mechanical properties of the lunch box. From the perspective of density, Comparative Examples 1 to 2 are higher than Examples 1 to 2. The use of wollastonite with a high aspect ratio needle-like structure and flaky talc can construct a fluffy network structure. For the production of quantitative lunch boxes, the density of the lunch box is reduced while the thickness is increased, further increasing the strength of the lunch box.

[0069] As can be seen from the above embodiments, the present invention provides a talc-wollastonite masterbatch and a preparation method thereof. The talc-wollastonite masterbatch of the present invention can be used to prepare disposable plastic products, and the obtained injection molded strips have more excellent mechanical properties. When applied to the production of disposable lunch boxes, the talc-wollastonite masterbatch of the present invention is degradable, and dust-free production is achieved. While ensuring that the gram weight of the lunch box meets the standard, the mechanical properties of the lunch box are improved, and the technical problems of poor environmental protection of the production of degradable plastic products and insufficient mechanical properties of degradable plastic products in the prior art are solved.

[0070] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A talc-wollastonite masterbatch, characterized in that: The invention is composed of the following components in parts by weight: 45-55 parts of polylactic acid, 25-35 parts of modified talc powder, 12-16 parts of modified wollastonite powder, 0.5-2 parts of antioxidant, 2-4 parts of stearic acid and 2-4 parts of lubricant.

2. The talc-wollastonite masterbatch according to claim 1, characterized in that: The number average molecular weight of the polylactic acid is 100,000 to 150,000.

3. A talc-wollastonite masterbatch according to claim 1 or 2, characterized in that: The antioxidant includes one or more of butylated hydroxyanisole, tert-butyl-4-hydroxyanisole and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; The lubricant includes one or more of calcium stearate, glyceryl stearate and PE wax.

4. The method for preparing talc-wollastonite masterbatch according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1): crushing talc ore to obtain talc powder, and then mixing it with coconut oil to obtain modified talc powder; crushing wollastonite ore to obtain wollastonite powder, and then mixing it with coconut oil to obtain modified wollastonite powder; Step 2): Modified talc powder, modified wollastonite powder, polylactic acid, antioxidant, stearic acid and lubricant are mixed, and the obtained mixture is extruded and pelletized to obtain talc powder-wollastonite masterbatch.

5. The method for preparing talc-wollastonite masterbatch according to claim 4, characterized in that: In step 1), the particle size of the talcum powder is 1000-1500 mesh, and the amount of coconut oil added is 0.8-1% of the mass of the talcum powder; The mixing is carried out under stirring, and the stirring speed is 3000-3600r / min.

6. The method for preparing talc-wollastonite masterbatch according to claim 5, characterized in that: In step 1), the particle size of the wollastonite powder is 600-800 mesh, and the amount of coconut oil added is 0.8-1% of the mass of the wollastonite powder; The mixing is carried out under stirring, and the stirring speed is 3000-3600r / min.

7. The method for preparing talc-wollastonite masterbatch according to claim 5 or 6, characterized in that: In step 2), the mixing is carried out under stirring, the stirring speed is 1000-1200 r / min, and the stirring time is 3-8 min; The temperature of the mixture is 120-130° C.; The extrusion is carried out in an extruder, the speed of the extruder is 650-750 r / min, and the feeding speed is 45-50 r / min; The extruder comprises 10 working sections, wherein the temperatures of the 10 working sections are independently 170-185°C, and the head temperature is 180-190°C.

8. The method for preparing talc-wollastonite masterbatch according to claim 7, characterized in that: In step 2), the pelletizing is carried out by water ring hot cutting process, and the length of the obtained masterbatch is 3 to 5 mm.

Citation Information

Patent Citations

  • Polylactic acid-modified grammite composite material and preparation method thereof

    CN101235194A

  • Fully degradable polylactic acid sheet material with high strength and high-temperature resistance, and preparation method thereof

    CN103540111A

  • Biodegradable polylactic acid based composite and application thereof

    CN103965596A

  • Functional master batch for reinforcing and toughening polylactic acid fibers and preparation method thereof and reinforcing and toughening polylactic acid material

    CN111534066A

  • Multifunctional filling modified polypropylene master batch as well as preparation method and application thereof

    CN115772296A

Cited By

  • Compound multifunctional auxiliary agent and application thereof in sheet preparation in polylactic acid

    CN120025596A

  • A compound multifunctional additive and its application in the preparation of polylactic acid sheets

    CN120025596B